2020
DOI: 10.3390/ma13204554
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Concrete Plates under Impact Load—Damage Quantification

Abstract: A large number of impact experiments have been carried out at the Technische Universität Dresden in recent years in several research projects. The focus was on reinforced concrete plates on the one hand and on subsequently strengthened reinforced concrete plates on the other hand. Based on these investigations, two fundamental tasks arose: (1) finding an objective description of the damage of components made of steel reinforced concrete that had previously been subjected to an impact load and (2) quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…TRC, also termed textile reinforced mortar (TRM), consists of fine-grained, cementitious matrices reinforced by continuous two- or three-dimensional textile meshes, usually made of carbon or glass multifilament yarns, and exhibits ductile, strain-hardening tensile behavior [ 9 , 10 , 11 , 12 ]. With regard to cyclic and highly dynamic loading, the geometric configuration of typical 2D and 3D textile reinforcements is not sufficiently fine to ensure dense crack patterns and high energy dissipation capacity, without substantial fragmentation and spalling of the cementitious matrix [ 13 ]. The latter can be mitigated by the addition of short, dispersed fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRC, also termed textile reinforced mortar (TRM), consists of fine-grained, cementitious matrices reinforced by continuous two- or three-dimensional textile meshes, usually made of carbon or glass multifilament yarns, and exhibits ductile, strain-hardening tensile behavior [ 9 , 10 , 11 , 12 ]. With regard to cyclic and highly dynamic loading, the geometric configuration of typical 2D and 3D textile reinforcements is not sufficiently fine to ensure dense crack patterns and high energy dissipation capacity, without substantial fragmentation and spalling of the cementitious matrix [ 13 ]. The latter can be mitigated by the addition of short, dispersed fibers.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the mechanical properties and coating of the textile reinforcement define to a large extent the tensile strength and the pre-peak deformability of the hybrid fiber-reinforced composites under investigation. The carbon textile exhibits high tensile strength and stiffness, both of which are essential for the strong confinement of the RC elements, both under quasi-static and severe dynamic loading [ 1 , 13 ]. However, the strain capacity of typical HS-SHCC is potentially higher compared to that of carbon yarns [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments described in subsequent studies, [9][10][11] which were also carried out at low impactor velocities, the formation of inclined shear cracks was the main failure criterion. Bangash 1 and Hering et al 6 distinguished between local and global damage in higher velocity impact scenarios. Local damage includes scabbing at the top and spalling at the bottom of the structural member.…”
Section: Cracking and Damage Processmentioning
confidence: 99%
“…On a large observation scale, a lot of different plate experiments were carried out by different researchers. Information on these experiments can be found for example in subsequent studies 5–8 . Besides plate tests, drop tower beam tests were often performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sound upscaling and application of the meso-level findings in the structural design involving SHCC should be supported by adequate numerical scale-linking models. This is due to the fact that the assessment and discrimination of various structural effects as inertia phenomena and complex fracture-mechanical mechanisms is hardly possible based on structural tests alone (see [6][7][8]). Multiscale methods represent a powerful tool to link the mesoscale and structural scale within the corresponding composite material.…”
Section: Introductionmentioning
confidence: 99%